São Luiz do Paraitinga: história, cultura e educação - Coninck, Lara Cristina Merlini (2014)
This study had as its main objective to examine the presence of preservation of the cultural identity of São Luiz do Paraitinga within its school environment. The research sought to contribute to the preservation of the town s cultural identity, highlighting for the school community the importance and wealth of its historic, folkloric, and cultural data, and the importance of schools in the preservation of local culture. From the starting point of gathering information about the town, its history, culture, rural culture, folklore, tangible and intangible cultural heritage (encouraged by Pesavento, Cascudo, Rios), tourism, celebrations, and natural events such as the flood of 2010, there followed a stepping into the school universe to become familiar with practices aimed at socialization/appropriation of the town s cultural characteristics. The town has nine schools located in rural and urban areas, from which were chosen five primary schools as the object of the research, the most central of which received a more detailed investigation, it having achieved good results in the Primary Education Development Index. The theoretical foundation involved the following themes; culture, school culture, the role of schools and teachers, education as culture, and the relationship between school and culture with authors such as Perrenoud, Brandão, Florestan Fernandes. Research was carried out by means of the following methods; participant observation, interviews, narratives, and document analysis relying on Bauer and Gaskell, Ludke and André. Participant observation brought a better understanding of the reality of the schools; availability of school places for pupils, data concerning registered pupils, school location, and especially projects developed regarding the research theme and the participation of teachers and students in the same. Documents analysed were sought in the schools and in the local education board. Interviews and narratives were employed with teachers and town residents who offered their opinions on the culture of the town and its preservation, their own experiences regarding this theme, and the presence in schools, or lack thereof, of projects aimed at preserving local culture. Existing school projects were analysed for the presence of local culture, folklore, and the preservation of cultural identity. Projects such as Rescuing the river , Holy Spirit Festival , Music of Elpídio dos Santos , and National Day were developed in four schools, with at least one project in each. Eight projects were developed in the focus school, highlighting the Memories and Identities project, obviously aimed at the dissemination and preservation of local culture. It was concluded that there is a concern for the presence of some form of local culture in schools, albeit with projects connected to celebrations and without pupil participation in their construction, and little participation in their development; the pupils are recipients of proposals and information. There is little community participation in schools, despite an increase in 2014. Generally there is no clear stance from schools, teachers, coordinators and principals with regard to the necessity of including specific activities tailored to the preservation of the town s cultural heritage. Thus, we see the need for investment in the dissemination of local culture in schools and in teacher training, that they may be involved effectively in the preservation of culture in São Luiz do Paraitinga.